Soil chemicals characterization of riparian area in Mariana sub-basin for environmental conservation - Thiago Rodrigo Cardoso da Silva; Maria Aparecida Pereira Pierangeli; Ricardo Keichi Umetsu; Mairo Fabio Camargo; Cassiano Garcia Roque (Revista Ambiente & Água, 2010)
This work aimed to characterize the soil chemical and particle-size of the riparian area of Mariana sub-basin in Mato Grosso state, comprised by the geographic coordinates 56º8’0’’W, 56º75’0’’W and 56º9’30’’S, 59º9’30’’S. The chemical and physical attributes evaluated were: pH (CaCl2), MO, K, P, Ca+2, Mg+2, H+, Al+3, V%, m%, SB, CEC pH 7.0, and particle-size and effective CEC. Nine plots of 20 × 50 m were installed in a way to represent the sub-basin full extent. The experimental design was completely randomized with 5 replicates for each depth. The analysis for soil fertility was performed using EMBRAPA methodology for routine analysis. Five samples were collected consisting of five sub-samples from each plot at depths of 0-0.1 and 0.1-0.2 m. The values obtained were subjected to variance analysis, the means tested by Tukey's test and correlations performed by the test T. The results show that the predominant soil texture is sand loam. The soil chemical properties were ranked low to medium fertility.